The construction of a new urban frontier: Scientific planning and metamorphosis of the satellite citie of Maipú through the MINVU and housebuilders. 1965-1976 - Riquelme Gálvez, Oscar (Cuadernos de Historia, 2023)
This urban history study reconstructs and explores the focused materialization of the actions of the Ministerio de la Vivienda y Urbanismo (MINVU) and the presence of the housing construction market that, between 1965-1976, participated in the scientific planning and urban metamorphosis of the satellite citie of Maipú. Thanks to the coordination of both actors, this periphery of the capital (Santiago de Chile) was transformed into a pole of urban development. This is analyzed using a mixed approach, from four computer moments (urban project, executors, construction work and inhabiting), and mainly, through the documents of the CORVI fund of the ARNAD.